Cryptic speciation in the "Marshallora nigrocincta" species complex (Gastropoda, Triphoridae) from the Western Atlantic. (25th February 2021) - Fernandes, Maurício Romulo; Salgueiro, Fabiano; de Paula, Thiago Silva; Lôbo‐Hajdu, Gisele; Pimenta, Alexandre Dias
Abstract: Marine gastropods of the " Marshallora nigrocincta " species complex range from southeastern Canada to southern Brazil, comprising M . nigrocincta, described from the northeastern United States, and Marshallora modesta, from the Caribbean. This study aims to disentangle this complex, elucidating how many species are indeed present in the western Atlantic, and whether M . nigrocincta is different from M . modesta . The mitochondrial markers COI and 16S were congruent in splitting the complex into six lineages: one belonging to M . nigrocincta (mainly from eastern United States), other two lineages related to M . cf. modesta (one from Florida, USA, and the second from Colombia), and three undescribed species from Brazil. Intra‐ and interspecific genetic distances, respectively, vary from 0–2.7%/6.3–13.5% ( COI ). The nuclear gene 28S was conservative to separate Marshallora sp. A (Brazil) from M . cf. modesta 2, but recognized M . cf. modesta 1, M . nigrocincta, and Marshallora sp. B (Brazil). The shell morphology is highly variable, but the presence of three basal cords seems to occur only in M . nigrocincta . The radular morphology exhibits a wide variation in the number of cusps of the central and lateral teeth. The new species herein identified will require formal descriptions following further fieldwork efforts, since the selected voucher material was lost during a fire. New generic allocations are made to Marshallora amicorum comb. nov., Marshallora pusilla comb. nov., and Marshallora medinae comb. nov., which is regarded as nomen dubium . This study may stimulate the incorporation of DNA analysis in the systematics of Triphoroidea, improving the knowledge about its biodiversity.